Analisis Program Tapera Berdasarkan Teori Keadilan John Rawls - Maulana, Difky; Syafitri, Nila; Al-Hambra, Sheva; Susanti, Revameila; Rifaldy, Edward; Ahmad, Rafael (CV Widina Media Utama, 2025)
This article analyzes the Public Housing Savings Program (Tapera) from the perspective of the theory of social justice developed by John Rawls. Tapera is an Indonesian government policy that aims to increase public access to decent housing through a mandatory contribution system for workers. This research uses a descriptive qualitative approach with a literature study method and secondary data analysis from official documents related to the implementation of Tapera. The results of the study show that although Tapera aims to create social justice in terms of home ownership, its implementation still leaves problems, especially for self-employed workers who are required to participate without an opt-out mechanism. In the context of Rawls' theory of justice, Tapera is in line with the principles of equal opportunity and protection of vulnerable groups, but has not fully fulfilled the principles of maximum freedom and fair distribution of benefits. Therefore, a thorough evaluation of the Tapera scheme and implementation is needed to ensure compliance with inclusive and non-discriminatory social justice values.ABSTRAKArtikel ini menganalisis Program Tabungan Perumahan Rakyat (Tapera) dari perspektif teori keadilan sosial yang dikembangkan oleh John Rawls. Tapera merupakan kebijakan pemerintah Indonesia yang bertujuan untuk meningkatkan akses masyarakat terhadap perumahan yang layak melalui sistem iuran wajib bagi pekerja. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode studi pustaka dan analisis data sekunder dari dokumen resmi terkait pelaksanaan Tapera. Hasil kajian menunjukkan bahwa meskipun Tapera bertujuan menciptakan keadilan sosial dalam hal kepemilikan rumah, pelaksanaannya masih menyisakan persoalan, khususnya bagi pekerja mandiri yang diwajibkan ikut serta tanpa mekanisme opt-out. Dalam konteks teori keadilan Rawls, Tapera sejalan dengan prinsip kesetaraan kesempatan dan perlindungan terhadap kelompok rentan, tetapi belum sepenuhnya memenuhi prinsip kebebasan sebesar-besarnya dan distribusi manfaat secara adil. Oleh karena itu, evaluasi menyeluruh terhadap skema dan pelaksanaan Tapera diperlukan untuk memastikan kesesuaian dengan nilai-nilai keadilan sosial yang inklusif dan non-diskriminatif.